Brittle cornea syndrome: current perspectives - Walkden A (Dove Medical Press, 2019)
Andrew Walkden,1,2 Emma Burkitt-Wright,3,4 Leon Au1,21Manchester Royal Eye Hospital, Manchester University Foundation Trust, Manchester, UK; 2Medical Academic Health Sciences Centre, University of Manchester, UK; 3Genetic Medicine, Institute of Human Development, Faculty of Medical and Human Sciences, University of Manchester, Manchester, UK; 4Genetic Medicine, St Mary’s Hospital, Central Manchester University Hospitals NHS Foundation Trust, Manchester Academic Health Science Centre, Manchester, UKAbstract: Brittle cornea syndrome (BCS) is a rare autosomal recessive connective tissue disorder characterised by severe corneal thinning, with the major ocular risk being spontaneous ocular perforation due to progressive stromal thinning and ectasia. It is a complex condition with limited treatment options. The purpose of this review is to highlight the difficulties associated with the condition and examine the available published evidence with regards to management.Keywords: brittle Cornea, spontaneous corneal perforation, corneal ectasia